Agglomeration, accessibility and productivity: evidence for large metropolitan areas in the US - Melo,PC; Graham,DJ; Levinson,D; Aarabi,S (Urban Studies, 2016)
This paper estimates the productivity gains from agglomeration economies for a sample of the largest metropolitan areas in the United States using measures of urban agglomeration based on employment density and employment accessibility. The latter is a more accurate measure of economic proximity and allows testing for the spatial decay of agglomeration effects with increasing travel time. We find that the productivity gains from urban agglomeration are consistent between measures, with elasticity values between 0.07 and 0.10. The large majority of the productivity gains occur within the first 20 minutes, and do not appear to exhibit significant nonlinearities.